Investigation the nexus between CO2 emissions, agricultural land, crop, and livestock production in Pakistan - Ali, Sajjad; Shah, Ashfaq Ahmad; Ghimire, Amogh; Tariq, Muhammad Atiq Ur Rehman (Frontiers in Environmental Science, 2022)
The ongoing adverse effects of climate change produced by carbon dioxide emissions have sparked global advocacy to face its adverse consequences with the utmost vigor. Pakistan’s contribution to global emissions is less than 1% while it is among the most vulnerable countries facing threat of climate change. The sources of carbon dioxide (CO2) emissions by particular nations must be understood to comprehend the procedures necessary to reduce emissions globally. This study is a contribution to empirics of the CO2 emissions, gross domestic product, crop production index, livestock production index, population, agricultural land, land under cereal crop and agriculture value-added. This study considered annual data from 1961 to 2014 for the country of Pakistan. We performed an Autoregressive distributed lag (ARDL) bound testing approach to investigate the long-run and short-run association among all research variables. To check the stationarity of the study variables, we also employed Augmented Dickey-Fuller and Phillips-Perron (P.P.) tests. The outcomes of the long-run estimates indicate that the coefficients of agricultural land and land under cereal crop have a positive and significant relationship with CO2 emissions, while the coefficients of crop production index have a negative and significant relationship with CO2 emissions, respectively. The outcomes from short-run estimates show that the coefficients of crop production index and livestock production index are both positive and statistically significant, which implies that these variables are crucial in boosting carbon emissions. The error correction model value is also negative and statistically significant, indicating the deviation of CO2 emissions to other variables from short-run to long-run equilibrium. According to the Pairwise Granger causality test, there is evidence of both unidirectional and bidirectional causation between the research variables. Based on the research outcomes, the government must carefully consider its regulations on agricultural and livestock production and embrace ecologically friendly techniques in the agriculture sector, which may minimize carbon emissions over time.